Portable and wearable self-powered systems based on emerging energy harvesting technology - Xu, Chen; Song, Yu; Han, Mengdi; Zhang, Haixia (Microsystems & nanoengineering, 2021)
A self-powered system based on energy harvesting technology can be a potential candidate for solving the problem of supplying power to electronic devices. In this review, we focus on portable and wearable self-powered systems, starting with typical energy harvesting technology, and introduce portable and wearable self-powered systems with sensing functions. In addition, we demonstrate the potential of self-powered systems in actuation functions and the development of self-powered systems toward intelligent functions under the support of information processing and artificial intelligence technologies.